Market Analysis for Cold storage Case Study PT Pos Logistics in Bandung City - Sulistiyaningsih, Febriani Puspita; Fayaqun, Reza; Numang, Irpan Puspita (Universitas Negeri Medan, 2023)
The use of cold storage has recently been in high demand among businesses, particularly those in the food and beverage industry. As one of the cold storage service providers, PT Pos Logistik wishes to determine the size of this business opportunity. Based on the findings of the survey and research, it was determined that cold storage users in the Bandung metropolitan region may be categorized into three groups: frozen foods, the processed food industry, and pharmaceuticals. As for market share percentage, the findings are as follows: 46% for frozen food, 46% for processed food, and 8% for the pharmaceutical industry. As a subsidiary of PT Pos Indonesia, PT Pos Logistik Indonesia already has a brand image, influencing 39.5% of purchasing decisions, while 60.5% of purchasing decisions are influenced by other variables not analyzed. The figure of 39.5% indicates that the influence of the brand image of Pos Logistik on the choice to acquire cold storage services is minimal